The impact of COVID-19 pandemics on dermatologic surgery: real-life data from the Italian Red-Zone. (17th February 2022) - Gironi, Laura Cristina; Boggio, Paolo; Giorgione, Roberto; Esposto, Elia; Tarantino, Vanessa; Damiani, Giovanni; Savoia, Paola
Abstract: Background: The COVID-19 pandemic is challenging healthcare systems worldwide. Dermatology had to re-prioritize visits, guarantee urgent care, and ensure continuity for chronic patients. Objectives: To evaluate the COVID-19 impact on dermatologic surgery outpatient management. Material and methods: In this real-life retrospective observational study, we evaluated both major and minor outpatient surgeries (MaOS and MiOS) performance in 2020, before and during the first month of lockdown declaration, in a primary referral center in Northern Italy. During the lockdown, all lifesaving and cancer surgery, (approximately 80% of our usual activities), were continued. Data from 2020 were compared with the 2019 corresponding periods to assess the real-life impact of COVID-19 in dermatologic surgical activities. Results: From January 1st to April 3rd, 2020 we performed 769 interventions, compared to 908 over the corresponding 2019 period. After the lockdown, scheduled surgeries were reduced by 14.8%; overall performed ones displayed a reduction of 46.5% (51.6% MaOS, 44.2% MiOS). 52.9% and 12.5% procedures were canceled due to patients' renunciation and due to confirmed/suspected COVID-19, respectively. Conclusions: While reduced in number, dermatologic surgeries, similarly to other surgical specialties, remained operative to provide oncological and/or life-saving procedures.